2021
DOI: 10.1007/s10389-021-01600-3
|View full text |Cite
|
Sign up to set email alerts
|

Perception and experiences regarding COVID-19 pandemic among urban young adults in Bangladesh: a mixed-method study

Abstract: Aim This study aimed at exploring the perception and experiences with regard to the COVID-19 pandemic among Bangladeshi urban young adults. Subject and methods Using a mixed-method approach, an online cross-sectional survey among 315 participants and in-depth interviews (IDI) among 20 young adults were conducted from May 1 to May 25, 2020. Descriptive statistics and chi-square tests were performed for quantitative data, along with the thematic analysis for qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Actually, in Japan the COVID-19 positive cases were most reported in those in their 20's (132,490 cases) and 30's (89,672 cases) among all the generations, consisting of 36.9% of all the positive cumulative cases and the rate has increased to around 50% after April 2021 at the time point of May 5, 2021(MHLW, 2021. The finding of a poor precautionary practice regardless of a better knowledge in young generation corresponds to a previous study in Bangladesh (Pervez et al, 2021). Therefore, improving the practices in the young age patients may improve and lower the high incidence of COVID-19 infection in these age groups.…”
Section: Discussionsupporting
confidence: 81%
“…Actually, in Japan the COVID-19 positive cases were most reported in those in their 20's (132,490 cases) and 30's (89,672 cases) among all the generations, consisting of 36.9% of all the positive cumulative cases and the rate has increased to around 50% after April 2021 at the time point of May 5, 2021(MHLW, 2021. The finding of a poor precautionary practice regardless of a better knowledge in young generation corresponds to a previous study in Bangladesh (Pervez et al, 2021). Therefore, improving the practices in the young age patients may improve and lower the high incidence of COVID-19 infection in these age groups.…”
Section: Discussionsupporting
confidence: 81%
“…Limited access to medical services was mentioned as a significant contributing reason for suicide behaviour during this outbreak by the majority of respondents (69.52%), which is consistent with findings from earlier studies (Raj et al 2021). According to additional research, the COVID-19 outbreak was brought on by a lack of healthcare facilities, and people also complained about the quality of the current medical services (Pervez et al 2021;Rahman et al 2020). In addition, our study found that bullying on social media increased the likelihood of suicidal conduct, and a prior study found a link between bullying victimization and suicidal behaviour (Garcia-Williams et al 2014).…”
Section: Discussionmentioning
confidence: 45%
“…In a previous study, rickshaw pullers explained their experience that the facilities and treatment provided to them in the government hospitals were not up to mark and not treated well ( Kumar et al., 2016 ). A previous study also revealed that even though most hospitals and health systems tend to recognize diagnostic errors as a serious safety concern, most organizations (even those that appear to be committed to patient safety) are still doing little to improve diagnosis ( Newman-toker et al., 2017 ), and dissatisfaction was also reported with the existing healthcare services in Bangladesh due to lack and not proper diagnostic testing facility ( Pervez et al., 2021 ). It is concerning that our study identified a substantial barrier that the existence and mastery of a broker (a person who serves as an intermediary) in hospitals frequently create barriers for patients seeking medical care.…”
Section: Discussionmentioning
confidence: 99%